Bilateral eyelid necrosis with dermal matrix reconstruction and skin grafting - Carlos Miguel Pereira; Irene Daher Barra; Kerly Abraão Badaró (Revista Brasileira de Cirurgia Plástica, 2021)
Skin and soft tissue infections are a group of pathologies of high prevalence. Necrotizing fasciitis is a rapid and destructive infection of the subcutaneous tissue and superficial fascia with high morbidity and mortality. It is frequent in the perineal region and of rare occurrence in the periorbital region. This report illustrates a case of bilateral eyelid necrosis after mild head trauma with abrasions. Intensive clinical treatment and surgical debridement of the affected area were performed. In the first phase of eyelid reconstruction, a dermal regeneration matrix was used. This cutaneous substitute initially described for burns is currently of great importance in plastic surgery, aiming to heal wounds better. Subsequently, cutaneous self-grafting was performed, and a good aesthetic and functional result was obtained.